Post‐1850 changes in Glacier Benito, North Patagonian Icefield, Chile. Issue 1 (20th November 2013) - Winchester, Vanessa; Sessions, Martin; Cerda, Jammie Valdivia; Wündrich, Olaf; Clemmens, Samuel; Glasser, Neil F.; Nash, Megan
Abstract Glacier Benito is a temperate outlet glacier on the west side of the North Patagonian Icefield. Rates of thinning and ablation were obtained using data collected by the British Joint Services Expedition in 1972/73 and subsequent data collected in 2007 and 2011. Ice‐front recession rates were based on dendrochronological dating for the terminal moraines and aerial and satellite imagery of the ice front in 1944, 1998 and 2002. Between the first Benito survey in 1973 and 2007, the lower glacier thinned by nearly 150 m at an average rate of 4.3 m yr−1 with the rate increasing to 6.1 m yr−1 between 2007 and 2011, a 28.7% increase during the latter period. Increases in ice movement and ablation were negligible: ice movement for 1973 and 2007 averaged 0.45 m day−1 and ablation averaged 0.05 m day−1. Ice front recession along the glacier's centre line from 1886 to 2002 was approximately 1860 m. Retreat rates between 1886 and 1944 averaged 8.9 m yr−1. Thereafter glacier asymmetry makes measurement along the glacier centre line unrepresentative of areal change until 1998 when symmetry was restored; retreat between 1944 and 1998 was 15.4 m yr−1. From 1998 to 2002 the rate increased dramatically to 127.2 m yr−1. Recession from the southern end of Benito's terminal moraine in the 1850s supports an early date for initial retreat of the Icefield's glaciers.